Pengaruh Penggunaan Model Cooperative Learning Tipe NHT Terhadap Hasil Belajar Tematik Terpadu Siswa Kelas IV SDN - Wizal, Mursyida; Miaz, Yalvema (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this study was carried out to determine the effect of the use of cooperative learning model Number Heads Together (NHT) on the integrated thematic learning outcomes of Class IV SDN 10 Sapiran Bukittinggi city. This research is an experimental type in the form of Quasi Experimental Type Nonequivalent Control Group Design. The population in this study were all students of class IV SD 10 Sapiran Bukittinggi city, totaling 56 students with sampling techniques using saturated samples. Data analysis techniques in this study used a prerequisite test in the form of normality and homogeneity tests and hypothesis testing using t-test (independent sampling-test). Observing the results of research that has been done, obtained tcount> ttable ie, 2.84891346> 2.004879275 with α = 0.05 which means Ha is accepted. The average student learning outcomes measured by posttest after learning, namely the experimental class 78.71 and the control class 70.05. So Ha accepted that there is a significant influence on the use of cooperative learning model number heads together (NHT) on the integrated thematic learning outcomes of Grade IV students of SDN 10 Sapiran, Bukittinggi. Keywords: Cooperative Model, Number Heads Together, Learning Outcomes, Integrated Thematic Learning, Conventional Learning.